SISTEM PAKAR DIAGNOSA PENYAKIT KULIT MENGGUNAKAN METODE FORWARD CHAINING PADA PONDOK PESANTREN ASHABURRATIB BERBASIS JAVA - Ricky Firmansyah; Zikriah (Journal of Research and Publication Innovation, 2024)
An expert system is an application of artificial intelligence that can assist in the process of disease diagnosis. This study developed an expert system for diagnosing skin diseases using the forward chaining method, implemented in the Java programming language. The system is designed for use at Pondok Pesantren Ashaburratib, aiming to provide a fast and user-friendly diagnostic tool. The knowledge base of the system consists of various medical rules related to common skin disease symptoms. Testing results indicate that the system is capable of diagnosing skin diseases with adequate accuracy and has potential for further development.